Thrombocytopenia limits the feasibility of salvage lomustine chemotherapy in recurrent glioblastoma: a secondary analysis of EORTC 26101 - Le Rhun, Emilie; Oppong, Felix Boakye; Van den Bent, Martin J.; Wick, Wolfgang; Brandes, Alba A.; Taphoorn, Martin J. B.; Platten, Michael; Idbaih, Ahmed; Clement, Paul M.; Preusser, Matthias; Golfinopoulos, Vassilis; Gorlia, Thierry; et al. (European journal of cancer, 2023)
Background: Thrombocytopenia represents the main cause of stopping alkylating chemotherapy for toxicity. Here, we explored the incidence, and the consequences for treatment exposure and survival, of thrombocytopenia induced by lomustine in recurrent glioblastoma. Methods: We performed a retrospective analysis of the associations of thrombocytopenia with treatment delivery and outcome in EORTC 26101, a randomised trial designed to define the role of lomustine versus bevacizumab versus their combination in recurrent glioblastoma.Results: A total of 225 patients were treated with lomustine alone (median 1 cycle) (group 1) and 283 patients were treated with lomustine plus bevacizumab (median 3 lomustine cycles) (group 2). Among cycle delays and dose reductions of lomustine for toxicity, thrombocytopenia was the leading cause. Among 129 patients (57%) of group 1 and 187 patients (66%) of group 2 experi-encing at least one episode of thrombocytopenia, 36 patients (16%) in group 1 and 93 (33%) in group 2 had their treatment modified because of thrombocytopenia. Lomustine was discontin-ued for thrombocytopenia in 16 patients (7.1%) in group 1 and in 38 patients (13.4%) in group 2. On adjusted analysis accounting for major prognostic factors, dose modification induced by thrombocytopenia was associated with inferior progression-free survival in patients with MGMT promoter-methylated tumours in groups 1 and 2. This effect was noted for overall sur-vival, too, but only for group 2 patients.Conclusion: Drug-induced thrombocytopenia is a ma-jor limitation to adequate exposure to lomustine chemotherapy in recurrent glioblastoma. Mitigating thrombocytopenia to enhance lomustine exposure might improve outcome in pa-tients with MGMT promoter-methylated tumours.(c) 2022 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/).
Gesehen am 15.05.2023